Nostalgia May Not Work for Everyone: the Case of Innovative Consumers - Barauskaitė, Dovilė; Gineikienė, Justina (Organizations and Markets in Emerging Economies, 2017)
In recent years, marketers have widely used nostalgia in their marketing strategies. However, little research has focused on understanding whether consumer responses to nostalgic communication are always positive. Seeking to fill this gap and referring to social identity theoretical framework, current research examines the relationship between nostalgia, innovativeness and consumer purchasing decisions. Empirical results demonstrate that innovativeness and nostalgia might indeed act in opposite directions. Managerial implications of the findings are considered and directions for future research suggested.
Keywords: consumer behavior; nostalgia; innovativeness